2022
DOI: 10.1101/2022.04.13.488170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Form follows function: Variable microtubule architecture in the malaria parasite

Abstract: The malaria parasite undergoes a series of extensive morphological changes within its human host and mosquito vector. A scaffold of microtubules beneath a peripheral double membrane establishes and maintains the distinct shapes of all infectious forms, but the underlying structural basis remains unknown. Here we applied in situ electron cryo-tomography after focused ion beam milling to follow changes in the microtubule cytoskeleton throughout the Plasmodium life cycle. This revealed an unexpected level of stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…Plasmodium , was limited to EM images of the apical end of invasive zoites 56, 57 . The presence of a reduced conoid in ookinete stages of P. berghei was only shown recently 25, 26, 28 . To investigate if Pcr4 and Pcr5 also localize to the PCRs in malaria parasites, both proteins were localized at multiple invasive stages throughout the Plasmodium lifecycle by integration of the coding sequence of mNeonGreen fused to triple-HA tag at the endogenous locus of each gene.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Plasmodium , was limited to EM images of the apical end of invasive zoites 56, 57 . The presence of a reduced conoid in ookinete stages of P. berghei was only shown recently 25, 26, 28 . To investigate if Pcr4 and Pcr5 also localize to the PCRs in malaria parasites, both proteins were localized at multiple invasive stages throughout the Plasmodium lifecycle by integration of the coding sequence of mNeonGreen fused to triple-HA tag at the endogenous locus of each gene.…”
Section: Resultsmentioning
confidence: 98%
“…Positioned in the vicinity of the APR, the conoid is a dynamic organelle composed of curved tubulin fibers forming an open cone, topped by preconoidal rings (PCRs) and traversed by two intraconoidal microtubules (ICMTs) 8 . Recent studies identified multiple conoid proteins in Plasmodium species and demonstrated the existence of a reduced conoid lacking ICMTs [25][26][27][28] . In Toxoplasma, the conoid extrudes and retracts through the APR in motile parasites, but how and why these movements take place is unclear [29][30][31] and whether conoid extrusion is required for microneme secretion 32 or rhoptry discharge is not known 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Homologues for most of the TgMAPs can be found in the genome of Plasmodium species, but none has been experimentally characterized for either asexual or sexual developmental stages so far. The presence of Plasmodium MAPs within the SPMT lumen has been suggested previously (39,40), but SPMT structures resembling those expected for PfSPM1, PfSPM2 and PfTRXL1 in SPMT lumen have only been identified recently by cryoEM and modelling, supporting that these proteins have a role in SPMT function (26).…”
Section: Introductionmentioning
confidence: 79%
“…The distance of microtubules to either the IMC or a membrane of a so far unknown origin were measured by taking the distance from the center of the microtubule to the inner side of the IMC or to the membrane, respectively. A cut-off value of 40 nm was set with distances of less or equal to 40 nm being considered as "close" according to Ferreira et al (26).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 1 more Smart Citation